Microstrip Line Fed Fractal Monopole Antenna with Defected Ground Structure - S. Mohan Reddy, S; M. Vinod Kumar, M; Sanjay, B; Aruna Kumari, K; V. S. Padma Rao, G (International Journal of Engineering and Technology, 2018)
This paper presents a wideband polarized antenna that is designed and analyzed for the cellular communication applications. The proposed antenna is designed with the coplanar wave guide feeding (CPW) by using the RT/ duroid 5880 material with a dielectric constant 2.2. It is observed that in the proposed model the return loss is -21.40dB for ungrounded CPW where as for the grounded CPW the loss is reduced to -39.13dB. The gain for the ungrounded CPW fed antenna is 2.95 dB and is enhanced to 3.2dB with  grounded CPW structure. It is observed that there is an improvement in the bandwidth upto 6.03 GhZ for grounded CPW when  DGS is applied. The antenna designing and simulation is done using ANSOFT HFSS software.